Rancang Bangun Sistem Pengaman Pintu Otomatis Berbasis Fingerprint Sensor dan Flask Web Server dengan Database Sqlite - Rizki Hadi Syarifudin; Arsito Ari Kuncoro; Budi Hartono (Jurnal Manajemen Informatika & Teknologi, 2026)
The following research aims to design and build an automatic fingerprint biometric door security system consolidated with a Flask web server and SQLite database, to overcome the weaknesses of conventional security systems such as manual keys (vulnerable to duplication) and passwords (single verification function and easy to break). This system was developed using a fingerprint sensor as a user identification and verification tool. Registered fingerprint data is stored in a SQLite database. The authentication process is controlled through the Flask web server which functions as an interface for user data management and door access control. This system is designed to meet the characteristics of biometric security: unique, not easily lost, unforgettable, and difficult to forge. The resulting system is able to distinguish between identification (who the user is) and verification (identity validation) functions through fingerprints. Compared to manual keys and a single password, this system offers a better level of security because it cannot be duplicated and does not depend on memorizing passwords. The use of a web interface allows flexible and centralized access rights management. The implementation of a fingerprint sensor combined with a Flask web server and SQLite database has proven effective in building an automatic door security system that is more reliable than conventional systems. This system has the potential to be applied in corporate environments to improve door access security.